2019
DOI: 10.1186/s41610-019-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preference of wild boar (Sus scrofa) for feeding in cool-temperate forests

Abstract: Background: The growing wild boar population has become a social issue and its feeding characteristics could affect the physical condition and the plant species composition in the South Korean forests. We aimed to reveal the preference of the wild boar on forest type and site condition as feeding grounds in two cool-temperate forested national parks, Odaesan and Seoraksan, in order to provide information to manage the growing population. Results: The 75 plots (53.6%) out of 140 plots were used as feeding groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Wild boar feed is dominated by plant material (90%) consumed in quite large proportions because of its large body (Ballari 2013). Wild boar has the habit of seriously exploring the forest floor in search of food (Lyang and Lee 2010; Kim et al 2019). Therefore, feeding activities will greatly affect the structure and function of forest ecosystems (Focardi et al 2000;Hone 2002;Kim et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Wild boar feed is dominated by plant material (90%) consumed in quite large proportions because of its large body (Ballari 2013). Wild boar has the habit of seriously exploring the forest floor in search of food (Lyang and Lee 2010; Kim et al 2019). Therefore, feeding activities will greatly affect the structure and function of forest ecosystems (Focardi et al 2000;Hone 2002;Kim et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it suppressed the reestablishment of S. borealis. To search for diet, wild boars excavate the underground to the extent that mineral soil is exposed, significantly removing S. borealis [50].…”
Section: Discussionmentioning
confidence: 99%
“…Populations of wild boar, as high reproductive omnivores, are increasing worldwide including in Korea due to the absence of predators, increased winter temperature, reduced snowfall, and increased Quercus forests [50,[88][89][90]. Traces of wild boar were very frequently found in forests [50]. This suggests that the synergistic effect can effectively act on forest regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have described the ecological traits of wild boars in South Korea using ecological methods have been published (Park and Lee 2003;Choi et al 2006;Lee 2013; Kim et al 2019). Although several studies about the dispersal ability of wild boars have been conducted in other countries, no such information is available in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…However, this research was conducted with a small sample size using the radio-tracking technique within a limited study area and time frame. Although a recent study about habitat preference demonstrated that wild boars prefer ridge mountain environments with substantial food resources (Kim et al 2019), further studies must establish detailed control strategies for diseases mediated by wild boars in South Korea. Because the spread of infectious diseases in wild animals is closely linked to the dispersal ability of the animals and the gene ow pattern within the frame of the population structure, information on the dispersal distance and pattern and the genetic structure of wild boars has the potential to contribute to the effective disease control strategy.…”
Section: Introductionmentioning
confidence: 99%